Clinical obstetrics & gynaecology - Magowan, Brian A. (Elsevier, 2019)
The fourth edition of this highly regarded textbook has been thoroughly overhauled. There is a new chapter bridging the gap between learning and doing (On-Call); new coverage of FGM and the Zika virus; sepsis has been updated; there is access to a further five chapters; there are ten videos to guide learners through the more difficult, complex issues they might face in O&G; and new self-assessment has been written to help with testing understanding.